MODELLING AND DESIGN OF ROBUST CONTROL FOR PASSANGER CAR SUSPENSION SYSTEM - KUSNANTO, A. (MILANG Journal of Mathematics and Its Applications, 2003)
There are many uncertainties that occur in characterizing systems and environment in which they have to operate. Due to the uncertainties, no classical control theories are applicable to systems properly. Because of that, new theories occur for solving the problem. One of the new theory is H∞ theory. In this paper, it is given the application of H∞ theory in design of controller. The controller will be applied to damp out the vibration of passanger car. In this works, the roughness of road is modelled as uncertainties.